Extended-Spectrum β-Lactamases in Human Isolates of Multidrug-Resistant Non-typhoidal Salmonella enterica - Sedrakyan, Anahit M.; Ktsoyan, Zhanna A.; Arakelova, Karine A.; Zakharyan, Magdalina K.; Hovhannisyan, Alvard I.; Gevorgyan, Zaruhi U.; Mnatsakanyan, Armine A.; Kakabadze, Elene G.; Makalatia, Khatuna B.; Chanishvili, Nina A.; Pirnay, Jean-Paul; Arakelyan, Arsen A.; et al. (Frontiers in Microbiology, 2020)
A total of 291 non-duplicate isolates of non-typhoidal Salmonella (NTS) were collected from the faecal samples of patients with salmonellosis in Armenia and Georgia during 1996-2016. The isolates were tested for resistance to antimicrobials, including extended-spectrum β-lactamases (ESBL). The high prevalence of multidrug-resistance (MDR) and ESBL-producer phenotypes was detected among Salmonella enterica subsp. enterica serovar Typhimurium (S. Typhimurium) isolates collected from patients in Armenia between 1996 and 2016. A total of 36 MDR NTS isolates were subjected to whole genome sequencing (WGS) to determine the genetic background of antimicrobial resistance (AMR) and mobile genetic elements. All ESBL-producing S. Typhimurium isolates belonged to the same sequence type (ST328). The ESBL-producer phenotype was associated with plasmid-encoded CTX-M-5 production. A range of other plasmids was associated with resistance to other antimicrobials, including the MDR phenotype.